Bubbles Quantified In vivo by Ultrasound Relates to Amount of Gas Detected Post-mortem in Rabbits Decompressed from High Pressure - Bernaldo de Quirós, Yara; Møllerløkken, Andreas; Havnes, Marianne B.; Brubakk, Alf O.; González-Díaz, Oscar; Fernández, Antonio (Frontiers in Physiology, 2016)
The pathophysiological mechanism of decompression sickness is not fully understood but there is evidence that it can be caused by intravascular and autochthonous bubbles. Doppler ultrasound at a given circulatory location is used to detect and quantify the presence of intravascular gas bubbles as an indicator of decompression stress. In this manuscript we studied the relationship between presence and quantity of gas bubbles by echosonography of the pulmonary artery of anaesthetized, air-breathing New Zealand White rabbits that were compressed and decompressed. Mortality rate, presence, quantity, and distribution of gas bubbles elsewhere in the body was examined postmortem. We found a strong positive relationship between high ultrasound bubble grades in the pulmonary artery, sudden death, and high amount of intra and extra vascular gas bubbles widespread throughout the entire organism. In contrast, animals with lower bubble grades survived for one hour after decompression until sacrificed, and showed no gas bubbles during dissection.